An Analysis of Moves in the Novel “The Old Man and The Sea” by Ernest Hemingway - Tyas, Sukma Wahyuning; Ginting, Rehdanana; Darmayanti, Darmayanti; Rangkuti, Linda Astuti; Fransiska, Widia (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study examines the discourse structure and interpersonal meaning in selected dialogues from The Old Man and the Sea, with a focus on moves and speech functions. Using a qualitative descriptive method, it applies Halliday’s moves and speech functions analysis to explore how grammatical forms, interrogatives, declaratives, and imperatives, perform pragmatic and interpersonal functions beyond their literal meanings. The analysis reveals a predominance of ‘k’ type moves or information exchange, including k2, k1, k1f, and k2f, over ‘a’ type moves or offers of service, which appear as a1, a1f, and a1. Declarative clauses are the most frequently used, encompassing structures such as RSQ, S, RRSQ, and AS. The findings highlight dynamic exchanges of knowledge and action, showing how dialogue advances the narrative and develops character relationships. Despite their brevity, Hemingway’s dialogues convey complex meanings, reflecting authentic interaction and his minimalist style. The study underscores the dual function of literary dialogue as a vehicle for both storytelling and social interaction.